The Role of Osteopontin in Tumor Progression Through Tumor-Associated Macrophages - Tan, Yuying; Zhao, Lei; Yang, Yong-Guang; Liu, Wentao (Frontiers in Oncology, 2022)
Osteopontin (OPN) is a multifunctional phosphorylated protein. It is widely involved in solid tumor progressions, such as intensification of macrophage recruitment, inhibition of T cell activity, aggravation of tumor interstitial fibrosis, promotion of tumor metastasis, chemotherapy resistance, and angiogenesis. Most of these pathologies are affected by tumor-associated macrophages (TAMs), an important component of the tumor microenvironment (TME). TAMs have been extensively characterized, including their subsets, phenotypes, activation status and functions, and are considered a promising therapeutic target for cancer treatment. This review focused on the interaction between OPN and TAMs in mediating tumor progression. We discuss the strategies for targeting OPN and TAMs to treat cancers and factors that may potentially affect the therapeutic outcomes of blocking OPN or depleting TAMs. We also discuss the role of cancer cell- vs. TAM-derived OPN in tumorigenesis, the mechanisms of how OPN affects TAMs recruitment and polarization, and why OPN could mediate anti-tumor and pro-tumor effects, as well as previously reported discrepancies.